PENGARUH KEBIJAKAN MONETER TERHADAP INFLASI DI INDONESIA (STUDI KASUS PRIODE TAHUN 2008 – 2013) - Misbahuddin Misbahuddin (Jurnal Bisnis dan Kewirausahaan, 2016)
The purpose of this study was to analyze the influence of the BI rate set by Bank Indonesia, the narrow money supply M1 and M2 broad money supply on the inflation rate in Indonesia. Thus, it is also intended to answer the question "whether the current monetary policy conducted by Bank Indonesia need or do not need to be done. Based on the analysis shown it can be said that all variables (BI rate, M2 and M1) only capable of influencing inflation of 18.9 per cent and the rest is explained by other variables outside of the model, such as Christmas, Eid and other holidays. Beredear money affects inflation in Indonesia, where the faithful a 1 percent increase in money supply (M1) increase inflation by 23, 6%.